Authentic Leadership and Improved Individual Performance: Affective Commitment and Individual Creativity’s Sequential Mediation - Duarte, Ana Patrícia; Ribeiro, Neuza; Semedo, Ana Suzete; Gomes, Daniel Roque (Frontiers in Psychology, 2021)
Authentic leadership has become increasingly important in the literature, attracting the attention of many scholars in the last decade. This study adopted an employee-centered perspective to guide its examination of the relationship between authentic leadership and individual performance and investigation of the sequential mediation of employees’ affective commitment and individual creativity. An analysis was conducted of data collected from 214 employees working in different business sectors. The results reveal a statistically significant positive relationship between authentic leadership and employees’ workplace performance, which are both directly connected and indirectly linked through the two proposed psychosocial mechanisms. The findings thus indicate that authentic leadership reinforces workers’ emotional connection with their organizations, thereby increasing their individual creativity and, subsequently, promoting better on-the-job performance. This study presents new and significant results since, on the one hand, it relied on a sequential mediation analysis of variables and, on the other hand, integrated the four main constructs into a single model. The proposed model displays the chain of effects between authentic leadership, affective commitment, individual creativity, and employee workplace performance. Implications for organizational management are discussed.